Selective oxidation of amaranth dye in soft drinks through tin oxide decorated reduced graphene oxide nanocomposite based electrochemical sensor. (July 2022) - Buledi, Jamil A.; Solangi, Amber R.; Hyder, Ali; Khand, Nadir H.; Memon, Saba A.; Mallah, Arfana; Mahar, Nasrullah; Dragoi, Elena Niculina; Show, Pau; Behzadpour, Marzyeh; Karimi-Maleh, Hassan
Abstract: The recent studies evaluated the extensive exploitation of azo dyes as food colorant to improve the texture of food to turn the food to be very attractive. The heavy consumption of the food colorants by the food industries in commonly consumed beverages especially in the soft drinks may become the cause of certain suspected diseases. Amaranth is an azo dye which easily cleaved into amines and is suspected to be mutagen and carcinogen. Thus, the quantification of amaranth through reliable and sensitive sensor is of great importance. The SnO2 /rGO nanocomposite has been engineered to be utilized as chemically modified sensor for the low-level quantification of amaranth in soft drinks and water sample. The fabricated nanocomposite materials was characterized through XRD, FTIR, raman and TEM tools which revealed average crystalline size of 23.7 nm, different surface functionalities and internal rectangle shaped morphology. The engineered nanocomposite was electrochemically characterized through electrochemical impedance spectroscopy (EIS) and Tafel plot to evaluate the electrocatalytic properties and charger transfer kinetics of SnO2 /rGO/Nafion/GCE. The resistance of bare, GO/GCE and SnO2 /rGO/Nafion/GCE was calculated as 812.5 Ω, 1343 Ω and 338 Ω. Certain parameters were optimized such as PBS electrolyte pH 6, scan rate 130 mV/s and potential window (0.4–1.2 V) to carry out sensitive and fluent determination process of amaranth azo dye. For the effectiveness of proposed sensor two calibration ranges were optimized from 1 to 800 nM and 1–60 μM. The LOD for both ranges were calculated as 0.68 nM and 0.0027 μM. Moreover, the anti-interference and stability profile of developed sensor were found phenomenal that suggest the exceptional electrocatalytic performance of SnO2 /rGO/Nafion/GCE for amaranth. Highlights: Fabrication of graphene oxide (GO) through Hammers method. Anchoring of SnO2 on graphene oxide sheets to fabricate SnO2 /rGO nanocomposite. Exploitation of SnO2 /rGO nanocomposite as conductive electrode material for ultra-sensitive determination Amaranth food colorant. Electrochemical characterization of SnO2 /Nafion/rGO/GCE through EIS and Tafel plot. Low level determination Amaranth dye in soft drinks.